2020
DOI: 10.1097/md.0000000000018969
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of acupuncture in post-stroke depression (PSD)

Abstract: Background: Post-stroke depression (PSD) is the most common emotional problem after stroke. It can lower the quality of life and increase the recurrence and mortality. Pharmacological agents have been shown to treat PSD. However, the benefits of pharmacotherapy are debatable and the side-effects are significant. More and more clinical trials suggest that acupuncture plays an important role in patients with PSD. The primary purposes of the study are to conduct a Bayesian analysis of randomized trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…The pathophysiology of PSD is remarkably complicated and, at present, poorly understood ( Villa et al, 2018 ; Chen et al, 2020a ); factors including both biological and psychosocial factors are likely to be involved. No single pathophysiological mechanism fully explains PSD ( Loubinoux et al, 2012 ).…”
Section: Pathophysiological Mechanisms Of Psdmentioning
confidence: 99%
“…The pathophysiology of PSD is remarkably complicated and, at present, poorly understood ( Villa et al, 2018 ; Chen et al, 2020a ); factors including both biological and psychosocial factors are likely to be involved. No single pathophysiological mechanism fully explains PSD ( Loubinoux et al, 2012 ).…”
Section: Pathophysiological Mechanisms Of Psdmentioning
confidence: 99%
“…Studies (Ng et al, 2007) have shown that the two most severe ischemic strokes are those in more than one vascular territory (MVT) and MCA. These strokes both cause severe neurocognitive impairments encompassing executive functions, memory, attention, and behavioral issues, such as depression, agitation, and abulia (van Lieshout et al, 2019;Busk et al, 2020;Chen et al, 2020;Draaisma et al, 2020;Syafrita et al, 2020). MCA strokes may even lead to further visuospatial cognitive impairments and impaired language.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, St. John's wort has been compared with other CAM treatments, such as acupuncture and massage. The two top recent keywords were "protocol" and "systematic review"; therefore, numerous studies and significant articles are expected to be published in in this field, including systematic studies [26][27][28][29][30][31]. Keyword analysis based on temporal order can reveal changes in processes in the fields of interest.…”
Section: Discussionmentioning
confidence: 99%